Variational bounds on the effective moduli of anisotropic piezoelectric composites - Gałka, A.; Gambin, B.; Telega, J.J. (Archives of Mechanics, 1998)
Inequalities of Thompson and Dirichlet type have been used to derive the elementary bounds on elastic, piezoelectric and dielectric macroscopic moduli. The Ritz method has been applied to determine approximately the effective moduli.